(untitled) (Global Journal of Management and Business Research, 2022)
The present research piece aims to determine customers satisfaction with services offered by rural banks in India The study has considered a total of 400 customers who are directly associated with the banks i e at least having one account with the banks using the purposive sampling method The opinion of the respondents on the selected variables indicating satisfaction dissatisfaction level was measured on a Likert scale